The Effects of General System Justification on Corruption Perception and Intent - Tan, Xuyun; Liu, Li; Huang, Zhenwei; Zheng, Wenwen; Liang, Yuan (Frontiers in Psychology, 2016)
Previous research stresses that system justifying belief can weaken corruption perception, by this possibly fostering unjust behaviors. However, general results of the effect of general system justification on corruption are ambiguous, indicating also a lessening impact. We conducted a line of studies trying to elucidate these circumstances by testing the effect of general system justification on corruption perception and intention. In addition, we explored institutional trust as a possible mediator in this process. For this purpose we conducted three studies. The first two studies examined the association between general system justification and corruption. In Study 1, a correlational design was run using questionnaires to assess the relation between general system justification and corruption perception as well as corruption intention. In Study 2, an experimental design was conducted manipulating general system justification via exposure to high or low system threat condition, then measuring its effect on corruption perception and corrupt intention. In Study 3, two sub-studies using correlational and experimental designs were run to explore the mediating role of institutional trust, respectively. Results replicated former studies showing that general system justification is negatively associated with corruption perception. However, they also showed a negative correlation with corrupt intention. Furthermore, they showed that institutional trust mediated the relation between general system justification and corruption. We suggest to consider these findings to further elucidate the psychological basis underlying different effects of general system justification on human behaviors.